KUASO BETINO RIMBO : Potret Perempuan dalam Keluarga Rimba - Ahmad Syarifin (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The relation between masculinity and femininity in the jungle family has a vital position. In inheritance case, a divorce, either life or death, causes several rights that belong to women such as child custody, property split (community or separate property. This nature resource inheritance status covers an ownership, utilization, and distribution for example in agricultural or hunted resource. However, social changes affect female (batino) role in a domestic field. She takes care not only for women responsibilities such as child care, household task, cooking and serving the husband, but also takes care of men’s responsibilities such as providing water from the river, collecting wood, farming and other activities that men should do. Keywords: power, women, and jungle familyCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.97